Biologically Based Restorative Management of Tooth Wear - Martin G. D. Kelleher; Deborah I. Bomfim; Rupert S. Austin (International Journal of Dentistry)
The prevalence and severity of tooth wear is increasing in industrialised nations. Yet, there is no high-level evidence to support or refute any therapeutic intervention. In the absence of such evidence, many currently prevailing management strategies for tooth wear may be failing in their duty of care to first and foremost improve the oral health of patients with this disease. This paper promotes biologically sound approaches to the management of tooth wear on the basis of current best evidence of the aetiology and clinical features of this disease. The relative risks and benefits of the varying approaches to managing tooth wear are discussed with reference to long-term follow-up studies. Using reference to ethical standards such as “The Daughter Test”, this paper presents case reports of patients with moderate-to-severe levels of tooth wear managed in line with these biologically sound principles.